Radiogenic Isotopes: The Case for Crustal Recycling on a Near-Steady-State No-Continental-Growth Earth [and Discussion] - R. L. Armstrong; R. S. Harmon (Philosophical transactions of the Royal Society of London. Series A: Mathematical, physical, and engineering sciences, 1981)
Pb, Sr and Nd isotopes define rock ages and residence times in mantle and continental crust, but are not diagnostic of either crustal growth or recycling in a near-steady-state Earth. Constancy of continental freeboard and uniformity of thickness of stable continental crust with age are the only two quantitative measures of crustal volume through time and these imply negligible crustal growth since 2.9 Ga B.P. Planetary analogies, Pb isotopes, atmospheric evolution, and palaeomagnetism also argue for early terrestrial differentiation. Rates of crustal growth and recycling are sufficient to reach a near-steady state over the first 1 Ga of Earth history, before widespread cratonization. Isotope compositions and ages of rocks are quantitatively compatible with near-steady-state recycling involving multiple complete reworkings of the crust by injection into the mantle along subduction zones. The recycling process can be observed to occur on the Earth today. Continental crust is uplifted, reduced in area, and thickened in orogenic belts. It is then subject to erosion, an effective isotopic homogenization process. A fraction of the sediment flux reaches the ocean floor or accumulates along continental margins, while soluble elements and water become fixed in ocean crust and trapped in sediments. Subduction of altered ocean crust, sediment, microcontinents and fragments of basement ripped off the edges of continents completes the process whereby continental crust, enriched in radiogenic Pb and Sr and with relatively unradiogenic Nd, is returned to the mantle. Pb, Sr and Nd isotopic compositions of igneous rocks from the mantle are explainable in terms of a near-steady-state model. The mantle buffer dominates observed isotope Sr and Nd evolutions. Mixing of crust and mantle causes all the isotope evolutions to approximate single-stage growth curves. Isotopic heterogeneity of the Earth increases as the rate of mixing declines. The observed escape of primordial $^{3}$He from the mantle is not evidence for continuing continental differentiation or against early differentiation of the Earth. Even if nearly complete equilibrium chemical differentiation occurred at 4.6 Ga B.P., some $^{3}$He would remain dissolved in the interior and would escape as recycling continued. A true steady state cannot be achieved because the driving energy declines with time and Earth surface processes have evolved with development of life and an oxygenated atmosphere. These unidirectional changes, plus variation in subduction rates and setting and style, and variation in rates of cratonization, provide a complex overprint on the near-steady-state background of continental evolution.